1994
DOI: 10.1097/00006123-199404000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aberrations in Human Brain Tumors

Abstract: Over the last decade, much has been learned about the genetic changes that occur in human neoplasia and how they contribute to the neoplastic state. Oncogenes and tumor suppressor genes have been identified, and many powerful molecular genetic techniques have emerged. Brain tumors have been intensively studied as part of this process. Specific and recurring genetic alterations have been identified and are associated with specific tumor types. In astrocytomas, for example, losses of genetic material on chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 148 publications
0
18
0
Order By: Relevance
“…Although one study reported resemblance at the molecular genetic level between ETs and astrocytic and oligodendroglial tumours (ATs and OTs)9, others reported that aberrations involved in the oncogenesis of ATs were rarely detected in ETs1, 4, 5, 19. OTs very frequently show loss of 1p and 19q8, 20–23.…”
Section: Discussionmentioning
confidence: 99%
“…Although one study reported resemblance at the molecular genetic level between ETs and astrocytic and oligodendroglial tumours (ATs and OTs)9, others reported that aberrations involved in the oncogenesis of ATs were rarely detected in ETs1, 4, 5, 19. OTs very frequently show loss of 1p and 19q8, 20–23.…”
Section: Discussionmentioning
confidence: 99%
“…evolution of gliomas and is important for the planning of rational therapeutic approaches at the molecular level. Most studies of this phenomenon in gliomas have focused on astrocytic tumors, and genetic models for tumor progression have been suggested (for reviews see 1,7,15,16,18,24 ). Malignant progression in oligodendroglial tumors, however, is still poorly understood, partly because techniques that have been used only reveal information about the region or gene of interest.…”
mentioning
confidence: 99%
“…Malignant progression in oligodendroglial tumors, however, is still poorly understood, partly because techniques that have been used only reveal information about the region or gene of interest. Analysis has revealed that LOH at chromosomes 1p and 19q is an early event in the oncogenesis of these tumors (for reviews see 1,6,7,15 ). Additionally, it has been proposed that malignant progression in oligodendroglial tumors might be accompanied by losses of genetic material on chromosomes 9p and 10, and EGFR amplification.…”
mentioning
confidence: 99%
“…In the past two decades, there has been an increasing number of studies devoted to the analysis of the cytogenetic characteristics of meningiomas 16–27. Many different genetic abnormalities have been identified in these tumors, those involving chromosome 22 such as monosomy 22/deletion of 22q being the most frequent ones 17, 28–30.…”
mentioning
confidence: 99%